Effect of the use of motor skill games in improving motor sensory perception in - mokrani, djamel (Journal of Social Sciences and Humanities, 2024)
The research aims to know the effect of the use of motor skill games to improve motorsensory perception in mentally handicapped children who are able to train, The researchers used the experimental approach to respond to research issues, on a sample of 20 averages mentally handicapped children(9-11)years, which is chosen at random, then we divided them into two equal groups 10 in each, control and experimental group, where the experimental group was subjected to the application of a set of tests of sensory and motor perception, and of a set of teaching units offered supervised by the researchers themselves; while the control group studied with the traditional program, once the raw results collected and treated statistically, It was found that the use of motor skills increased the sensory and motor perception of the mentally handicapped, we advise you, therefore, designed a kinetic and sports program to develop cognitive sensory capacities for mentally handicapped children who are able to train by focusing on motor skill games.